Ashraf 'Ali al-Tahanawi wa juhudihi fi al-tarabat bayna al-hadith wa al-tasawwuf khilal kitabuhu "Haqa'iq al-tariqah min al-sunnah al-aniqah" = Ashraf Ali al-Tahanawi and his effort in linking between hadith and sufism through his book Haqiqat al-tariqat min al-sunnah al-aniqah / Muhammad Iqlim al-Rida' - al-Rida', Muhammad Iqlim (2011)
This study highlights the personality of Shaikh al-Thanawi and his efforts to establish the relationship between the Prophetic Traditions and Tasawwuf (mysticism) in his book“ Haqiqah al-Tariqah min al-Sunnah al-Aniqah”. Therefore, this research aims to shed focus on this personality along with studying his intellectual, religious and reformative life in a brief manner. Afterwards, it will attempt to compile some selected prophetic traditions that are narrated in this book. In an attempt to clarify the strong association between the Prophetic Traditions and Mysticism based on quoted statements of contemporary scholars in explaining those Prophetic Traditions. The researcher has adopted several research methodologies in carrying out the study such as inductive, analytical and practical approaches. Hence, some Prophetic Traditions along with mentioning their references and authenticated sources are compiled in this research. The researcher has attempted to identify their degrees in terms of acceptance and rejection, and later investigated the validity of those Prophetic Traditions with regard to the study of Mysticism. An attempt to reconcile and adjustment between the Mystic thoughts and the thoughts of general Hadith scholars regarding some issues of Mysticism has been made there supported by the statements of various Hadith scholars and the early Muslim scholars. Moreover, this research will concentrate on studying the balanced method of Shaikh al-Thanawi through his distance from the excesses and negligences in religious matters. This research is summarized in uncovering some significant findings that, the Mysticism has an inherent association with the Prophetic Traditions, as itself resembles a call to a balanced and intermediate religion. The study will end by mentioning the major findings, recommendations and suggestions.